The INO80 complex activates the transcription of S‐phase genes in a cell cycle‐regulated manner - Knezevic, Iva; González‐Medina, Alberto; Gaspa, Laura; Hidalgo, Elena; Ayté, José (The FEBS journal, 2018)
Chromatin structure is an essential factor in the proper regulation of DNA repair, DNA replication and transcription. The INO80 complex and the SWR complex have been shown to play a fundamental role in transcription regulation through remodeling chromatin at specific genes and loci. Here, we report that the Schizosaccharomyces pombe INO80 complex physically interacts with the mlui‐binding factor (MBF) complex. Furthermore, we are able to detect the INO80 complex in MBF‐regulated promoters. Binding of INO80 to these genes is cell cycle regulated, with a maximum binding preceding their transcription and accumulation of their mRNAs. In fact, the INO80 complex is required to fully and timely activate the transcription of these genes. We also show that the accumulation of acetylated H2A.Z at the +1 nucleosome is cell cycle regulated. Cells in which H2A.Z acetylation is abolished still have some cell cycle‐regulated transcription of MBF‐dependent genes, although to a much lesser extent. The G1‐to‐S transcriptional wave is required to induce the expression of genes necessary for DNA synthesis. This is achieved by the coordination of specific transcription factors, like the mlui‐binding factor complex in fission yeast, and chromatin remodelers, like the INO80 complex. The interaction between both complexes is cell cycle regulated, allowing the timely expression of specific genes.